Antenatal Screening for Group B Streptococcus in the Setting of Preterm Premature Rupture of Membranes: Empiric versus Culture-based Prophylaxis - Mithal, Leena B.; Shah, Nirali; Romanova, Anna; Miller, Emily S. (American Journal of Perinatology Reports, 2020)
Objective Imperfect culture sensitivity and increase of early onset neonatal sepsis (EONS) risk in preterm neonates raise concern that culture-based intrapartum antibiotic prophylaxis (IAP) may be insufficient after preterm premature rupture of membranes (PPROM). Our objective was to compare rates of EONS after empiric versus culture-based IAP in PPROM.Study Design This retrospective cohort study included women with a singleton gestation and PPROM between 23 and 33 weeks. Outcomes after culture-based IAP were compared with empiric IAP. The primary outcome was EONS. Secondary outcomes included group B streptococcus (GBS) bacteremia, bacteremia, and neonatal GBS infection. Bivariable and multivariable logistic analyses were performed.Results Of the 270 women who met inclusion criteria, 136 (50%) had culture-based IAP of whom 36 (26.5%) were GBS positive. There was no significant difference in bacteremia (2.2 vs. 4.5%, p = 0.30), GBS infection (0.8 vs. 0.7%, p = 1.00), or EONS (11.8 vs. 12.7%, p = 0.82) in infants of women with culture-based IAP compared with empiric IAP. Multivariable analysis confirmed a lack of advantage to empiric versus culture-based IAP in EONS risk (adjusted odds ratio [aOR] = 0.82, 95% confidence interval [CI]: 0.44–1.93).Conclusion In pregnancies complicated by PPROM, infants of women who received culture-based IAP had no significant difference in EONS or GBS infection compared with infants of women with empiric IAP.
Keywords: preterm premature rupture of membranes; early onset neonatal sepsis; group B streptococcusculture